2006
DOI: 10.1099/vir.0.82121-0
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characterization of the largest mycoviral-like double-stranded RNAs associated with Amasya cherry disease, a disease of presumed fungal aetiology

Abstract: The sequence of the four large (L) double-stranded RNAs (dsRNAs) associated with Amasya cherry disease (ACD), which has a presumed fungal aetiology, is reported. ACD L dsRNAs 1 (5121 bp) and 2 (5047 bp) potentially encode proteins of 1628 and 1620 aa, respectively, that are 37 % identical and of unknown function. ACD L dsRNAs 3 (4458 bp) and 4 (4303 bp) potentially encode proteins that are 68 % identical and contain the eight motifs conserved in RNA-dependent RNA polymerases (RdRp) of dsRNA mycoviruses, having… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
24
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 17 publications
1
24
0
Order By: Relevance
“…Its genome encompasses four segments but all of which are much larger than those of chrysoviruses (Figure 4). Interestingly, the genome of Amasya cherry disease-associated mycovirus (ACDAV) also encompasses four segments but two of which putatively encode RdRps that are related to each other [36] and which cluster with RnQV1 in the phylogenetic tree (Figure 3). It has been suggested that the two RdRps of ACDAV might derive from two related viruses [35].…”
Section: Resultsmentioning
confidence: 99%
“…Its genome encompasses four segments but all of which are much larger than those of chrysoviruses (Figure 4). Interestingly, the genome of Amasya cherry disease-associated mycovirus (ACDAV) also encompasses four segments but two of which putatively encode RdRps that are related to each other [36] and which cluster with RnQV1 in the phylogenetic tree (Figure 3). It has been suggested that the two RdRps of ACDAV might derive from two related viruses [35].…”
Section: Resultsmentioning
confidence: 99%
“…The more abundant mycoviruses with double-stranded RNA (dsRNA) genomes are generally classified into five major families: Totiviridae (nonsegmented, 4.6-7 kbp), Partitiviridae (2 segments, 1.4-2.3 kbp), Chrysoviridae (4 segments, 2.4-3.6 kbp), Reoviridae (10-12 segments, 0.7-5 kbp), all of which are conventionally encapsidated, Megabirnaviridae (2 segments, 7-9 kbp), and the proposed families "Quadriviridae" (4 segments, 3.7-4.9 kbp) and "Alternaviridae" (4 segments, 1.4-3.6 kbp) (1)(2)(3)(4)(5)(6)(7)(8). The remaining six families (Alphaflexiviridae, Barnaviridae, Endornaviridae, Gammaflexiviridae, Hypoviridae, and Narnaviridae) accommodate single-stranded RNA (ssRNA) genomes, of which only three families (Alphaflexiviridae, Barnaviridae, and Gammaflexiviridae) form virus particles, whereas members of the remaining three virus families are unencapsidated and do not form typical virions.…”
mentioning
confidence: 99%
“…However, the sequences of other novel dsRNAs (L1 and L2) do not code for RdRPs and thus justify the novel status of these viruses until their mode of replication and relationships with L3 and L4 DsRNAs are fully established. We have aligned our sequences obtained on RdRp translations of the dsRNA (size), which show similarity to those of the published sequences (Kozlakidis et al, 2006). Interestingly, BLASTn alignments of deduced RdRP (RNA dependent RNA Polymerase) sequences of MVX-mushroom dsRNAs exhibited highest similarity also with RdRPs of PRD1 phage (host: Salmonella typhimurium), fowl plague virus and to those of dsRNA carrying Cryptosporidium baileyi (poultry biotype), some of which are known to occur in chicken litter, an ingredient of the compost for mushroom cultivation.…”
Section: Presumptive Defective Virus-like Particle Formationsmentioning
confidence: 99%
“…It may be worthwhile to overview our findings to those of the new viruses with presumed fungal aetiology such as the Amasya cherry disease. Dr Bob Coutts group at the Imperial College, London, (Kozlakidis et al, 2006) recently achieved molecular characterization of two new viruses via sequencing of two largest (novel) dsRNAs (L3, L4) of ACD whose translated RNA dependent RNA polymerase (RdRP) regions had high similarity with other members of the Totoviridae. However, the sequences of other novel dsRNAs (L1 and L2) do not code for RdRPs and thus justify the novel status of these viruses until their mode of replication and relationships with L3 and L4 DsRNAs are fully established.…”
Section: Presumptive Defective Virus-like Particle Formationsmentioning
confidence: 99%
See 1 more Smart Citation